Analisis Pola Asuh Orang Tua dalam Mendampingi Anak Belajar Selama Pandemi COVID-19 - Wahyu Utama; Suprapto Suprapto (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
This study aims to analyze about the effectiveness of online learning of elementary school students in neighbourhood RT.009/03 Kebagusan during Covid-19 pandemic. This study used a qualitative exploratory method and the research approach used a qualitative case study method which was used to obtain information on the constraints and consequences of the Covid-19 pandemic on student learning at home. In this study, there were 5 respondents who lived in the neighborhood RT.009/03, Kebagusan. To maintain the confidentiality of the respondent's identity, the researcher gave the names of the respondents R1, R2, R3, R4, and R5. The results of this study are that there are several obstacles experienced by parents in online teaching and learning activities, namely the mastery of technology is still lacking, the addition of internet quota costs.